Bluetongue strikes again (translation) (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
For the second year in a row, bluetongue has struck in Western Europe. The livestock industry in the Netherlands, Germany, France, Belgium and Luxemburg is again weighed down by the international measures caused by this disease. Bluetongue is a viral disease that is on the list of the international organization for controlling animal diseases, OIE. In the case bluetongue, this means controlling the disease on operations by keeping animals indoors, by disinfecting, and by establishing a 20-kilometre zone around an affected farm. In addition there is a 150-km protection zone, in which stricter controls and hygiene measures are enforced. Cattle, semen and embryos are not allowed to be transported to areas outside the 20-kilometre zone unless a series of test have taken place and the animals have been treated with a disinfectant against midges. The exporters of live cattle have voluntarily adopted extra measures in order to be able to supply guaranteed bluetongue-free animals to their clients. The OIE would have to take bluetongue off of the list of diseases that require intensive measures. All the more in view of the fact that vaccinating against bluetongue is possible.